PERSEPSI MAHASISWA TERHADAP MUTU PELAYANAN AKADEMIK DI JURUSAN ADMINISTRASI NIAGA POLITEKNIK NEGERI MALANG - Tri Yulistyawati Evelina; Rena Feri Wijayanti; Ahmad Fauzi (Adbis: Jurnal Administrasi dan Bisnis, 2018)
The research aims to: examine the quality of academic service quality (tangibles, reliability, responsibility, assurance, and empathy) influencing student satisfaction at the Malang State Polytechnic Business Administration Department. The subjects in this study are Business Administration students, there are 2 (two) academic services, namely Academic Administration for D3 Business Administration Program and DIV Marketing Management. The type of data used is primary data (questionnaire) and secondary data. The results show that the influence of the variables studied is 72.2%. and each Service Quality variable, namely Tangibles, Reliability, Assurance and Emphaty has a significantly positive effect on Student Satisfaction, but for the Responsiveness variable it shows a significant negative effect on Student Satisfaction.